Differential aspects of collaborative work in new cooperative experiences in the social and solidarity-based economy - Santamaría-L´ópez, Elsa; Carbajo-Padilla, Diego (Iberoamerican Journal of Development Studies, 2023)
Although collaborative work has a long tradition in a large part of the cooperative movement, the processes of labour precariousness in recent years, together with phenomena such as entrepreneurship and social innovation, have made these forms of work more visible and relevant. Based on a sociological approach and a qualitative methodology, three cases of recently formed organisations, which represent new experiences of cooperativism with social aims, are discussed. The article explores the conditions in which collaboration takes place and identifies some of the most significant paradoxes, tensions and discomforts that take place in these working environments. Finally, it reflects on how these collective strategies are shaping work and life alternatives that try to resist the processes of individualisation and precarisation in which they are developed.